2022
DOI: 10.3389/fcimb.2022.964469
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of traditional Chinese medicine treating hepatitis B virus-related hepatocellular carcinoma based on target-driven reverse network pharmacology

Abstract: Hepatocellular carcinoma (HCC) is a serious global health problem, and hepatitis B virus (HBV) infection remains the leading cause of HCC. It is standard care to administer antiviral treatment for HBV-related HCC patients with concurrent anti-cancer therapy. However, a drug with repressive effects on both HBV infection and HCC has not been discovered yet. In addition, drug resistance and side effects have made existing therapeutic regimens suboptimal. Traditional Chinese medicine (TCM) has multi-ingredient and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The liver was responsible for regulation and promotion. The lung was responsible for purification and descent [ 26 ]. The two organs complement each other to coordinate qi, blood and body fluid, and restore non-pathological state [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The liver was responsible for regulation and promotion. The lung was responsible for purification and descent [ 26 ]. The two organs complement each other to coordinate qi, blood and body fluid, and restore non-pathological state [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we found that these 306 targets were composed of 25 HCC targets and 281 non-HCC targets. Since TCM has the characteristics of multitarget pharmacological action, it can not only act on disease genes directly but also exert the therapeutic effect of HCC by acting on other related genes [ 24 , 45 ]. Figure 4(a) implies that most compounds are intensively linked to multiple targets.…”
Section: Resultsmentioning
confidence: 99%